Coloring Mechanisms and Archaeometric Identification of Ancient Black Pottery: A Cross-Cultural Review - Jia, Yuqi (Scientific Journal of Technology, 2026)
Black pottery is widely attested across Neolithic China and the Classical Mediterranean, yet the physicochemical origins of its black coloration differ substantially between these regions. This review classifies ancient black pottery firing techniques into four categories based on coloring mechanism: (1) reduction firing, where iron oxides are converted to magnetite or wüstite under oxygen-depleted conditions; (2) carbon infiltration, where free carbon from incomplete combustion deposits in the ceramic body; (3) three-stage oxidation–reduction–reoxidation firing, which produces black iron-based glass-ceramic coatings; and (4) burnishing, where directional alignment of platy minerals suppresses diffuse reflection. For each category, we review formation mechanisms, archaeological examples, and diagnostic microstructural features. A hierarchical analytical framework is then presented, ranging from non-destructive screening to micro-area quantitative analysis. Common pitfalls including post-depositional alterations and equifinality in technique attribution are discussed, alongside emerging techniques such as synchrotron micro-X-ray diffraction, X-ray absorption near-edge structure spectroscopy, and micro-computed tomography. Cross-cultural comparison reveals that Chinese and Mediterranean potters developed parallel yet distinct strategies for controlling kiln atmosphere and surface microstructure.